Sacred Misinterpretation: Reaching Across the Christian-Muslim Divide - Accad, Martin (William B. Eerdmans Publishing Company, 2019)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Figures -- Foreword by Gabriel Said Reynolds -- Preface -- 1. Introduction -- Christian-Muslim Interaction -- The Context of My Writing -- What Does Theology Have to Do with Conflict and War? -- The Kerygmatic Approach to Christian-Muslim Interaction -- The Islamic Phenomenon -- Islam's Prophet in the Kerygmatic Approach -- The Qurʼan in the Kerygmatic Approach -- Muslims in the Kerygmatic Approach -- Purpose of Relationship with Islam and Muslims -- Methods Used in the Kerygmatic Approach to Islam and Muslims -- Expectable Outcomes -- A Legitimate Insider's Knowledge of Islam -- The Suprareligious Approach and the "Two-Buildings" Analogy -- A Book Respectful Enough of Islam for Muslims to Read It -- A Biblical Theme: God's Agenda -- Understanding the Importance of Mercy -- Adopting an Attitude of Humility -- Seeking Ways to Act Justly -- Mercy, Humility, and Justice in the Context of Lebanon -- Political Conflict and the Role of Religious Dialogue -- 2. Hermeneutics and Dialogue -- Christian Misrepresentation: Reading Christian Thinking into the Qurʼan -- Christian Misrepresentation: Giving Primary Attention to Literary Context -- Muslim Misrepresentation: Reading the Bible Muhammado-centrically -- Comparative Observations on Textual Interpretation -- The Legitimate Interpretation of the Qurʼan -- Language and Grammar -- Occasions of the Revelation -- Interpretation Proper -- Stories of the Prophets and the Biography of Muhammad -- Identification of the Obscure -- The Theory of Abrogation -- An Argument against the Claim of Medinan Abrogation -- Tradition versus Opinion -- Legitimate Christian Interpretation of the Qurʼan -- The Importance of Context -- Interpretation and the Emergence of Doctrine -- Historical Context.